Fractionation of DMSO-Extracted and NaOH-Extracted Hemicelluloses by Gradient Ethanol Precipitation from Neosinocalamus affinis - Genque Fu; Panpan Yue; Yajie Hu; Nan Li; Zhengjun Shi; Feng Peng (International Journal of Polymer Science)
Neosinocalamus affinis hemicelluloses were extracted with pure DMSO and 3% NaOH in sequence. The DMSO- and NaOH-extracted hemicelluloses were then successively fractionated by gradient ethanol precipitation. NaOH-extracted hemicellulosic fractions with different branch degree could be separated by gradient ethanol precipitation, while DMSO-extracted hemicellulosic fractions could not. FT-IR spectra showed that DMSO-extracted fractions have more complete structure, while NaOH-extracted fractions have no acetyl at all. The FT-IR and NMR revealed that the DMSO-extracted Neosinocalamus affinis hemicelluloses were 4-O-methyl-glucuronoarabinoxylans consisting of a linear (1→4)-β-D-xylopyranosyl backbone with branches at O-2,3 of acetyl, O-2 of 4-O-methyl-a-D glucuronic acid, and O-3 of arabinose.